The EU-CEAP impacts on developing countries: An analysis of the plastic packaging, electric vehicles and batteries sectors - Jenny To (German Institute of Development and Sustainability (IDOS), 2022)
The European Union Circular Economy Action Plan (EU-CEAP) is key to transitioning to a circular economy and climate neutrality under the EU Green Deal - and developing and emerging countries (DECs) play important roles, They are essential for primary material chains, for example, for electric vehicle batteries, DECs are also part of secondary material chains, and Europe relies on them to recycle its plastic packaging, Despite the crucial roles that DECs play in Europe's transition to a circular economy, literature and policy discourses have not yet examined the EU-CEAP's impact, This discussion paper fills this gap by outlining the EU- CEAP's challenges and opportunities for DECs and presents recommendations for development cooperation.
Keywords: 330; circular economy; green economy; EU Green Deal; EU Circular Economy Action Plan; plastic waste; plastic packaging; electric vehicles; electric vehicle batteries; developing and emerging countries